Implementation of Lean Warehouse to Minimize Wastes in Finished Goods Warehouse of PT Charoen Pokphand Indonesia Semarang - Puspitasari, Nia Budi; Ardila, Audy Yumna (ComTech: Computer, Mathematics and Engineering Applications, 2016)
PT. Charoen Pokphand Indonesia Semarang is one of the largest poultry feed companies in Indonesia. To store the finished products that are ready to be distributed, it needs a finished goods warehouse. To minimize the wastes that occur in the process of warehousing the finished goods, the implementation of lean warehouse is required. The core process of finished goods warehouse is the process of putting bag that has been through the process of pallets packing, and then transporting the pallets contained bags of feed at finished goods warehouses and the process of unloading food from the finished goods warehouse to the distribution truck. With the implementation of the lean warehouse, we can know whether the activities are value added or not, to be identified later which type of waste happened. Opinions of stakeholders regarding the waste that must be eliminated first need to be determined by questionnaires. Based on the results of the questionnaires, three top wastes are selected to be identified the cause by using fishbone diagram. They can be repaired by using the implementation of 5S, namely Seiri, Seiton, Seiso, Seiketsu, and Shitsuke. Defect waste can be minimized by selecting pallet, putting sack correctly, forklift line clearance, applying working procedures, and creating cleaning schedule. Next, overprocessing waste is minimized by removing unnecessary items, putting based on the date of manufacture, and manufacture of feed plan. Inventory waste is minimized by removing junks, putting feed based on the expired date, and cleaning the barn